Advancing family theories - White, James M. 1946- (SAGE, 2005)
Explores two contemporary theories of the family-rational choice theory & transition theory that illuminate what differing theories reveal about families. The book also discusses how meta-theories can assist in refining theory, & offers insight on the 'understanding versus explanation' debate